Analysis of Mathematical Problem Solving Ability through the Use of School Cooperative Context as an Innovative Contextual Approach in Learning Straight Line Equation Material - Titin Wijayanti; Zulkardi Zulkardi; Ely Susanti; Meryansumayeka Meryansumayeka (Universitas Pendidikan Mandalika, 2025)
The purpose of this study was to describe the mathematical ability of grade VIII students at SMP Negeri 2 Sungai Keruh, Musi Banyuasin Regency in solving problems on the material of straight line equations by using the context of school cooperatives where school cooperatives provide an authentic context-based learning environment, allowing students to directly apply the concepts they have learned, including in the field of mathematics. Students' ability to solve mathematical problems plays an important role in determining the level of student success in learning. The subjects this study involved 30 students who were class VIII students. To describe in depth the students' ability to solve problems, a comprehensive approach is needed that not only includes the final results, but also the thought processes and strategies they use in solving these problems. With descriptive method and qualitative approach is the type of this research. The tool instrument in this study used in the form of an instrument to do a test on the ability solve mathematical problems with the material straight line equations as much as 2 activities of problem test activities and in the form of interviews. The level of students' ability to solve math problems at each Polya stage is as follows. 27% of students are categorized as high ability, 50% of students with medium ability and 23% of students with low ability to solve problems. In general, this situation illustrates that students' ability to solve mathematical problems is at a moderate level. These results illustrate that students' ability to solve mathematical problems can be improved through a more contextualized direct approach where problem-based learning helps students understand mathematical concepts by linking theory to real situations, encouraging students to think critically in solving problems directly using problems that are very relevant in everyday life.